CROSS-MATCHING OF VERY LARGE CATALOGS - Martynov, M. V.; Bodryagin, D. V. (Одеські астрономічні публікації, 2016)
Modern astronomical catalogs and sky surveys, that contain billions of objects, belong to the “big data” data class. Existing available services have limited functionality and do not include all required and available catalogs. The software package ACrId (Astronomical Cross Identification) for cross-matching large astronomical catalogs, which uses an sphere pixelation algorithm HEALPix, ReiserFS file system and JSON-type text files for storage, has been developed at the Research Institution “Mykolaiv Astronomical Observatory”